The Use of Project Based Learning in Microteaching Courses to Instill Students' Creative Thinking Ability - Sukiman, Sukiman; Priyatni, Endah Try; Suwignyo, Heri (Jurnal Pedagogi dan Pembelajaran, 2023)
The low creativity of students in the microteaching lecture process is indicated by the fact that many students still need help preparing lesson plans, teaching materials, and student worksheets. In addition, students arrange learning administration based on what is on the internet without any modifications. To overcome these problems, it is necessary to apply the right learning model to increase student creativity. This research aims to develop students' ability to create creative learning administration by utilizing project-based learning models in microteaching courses. This research is a type of qualitative research using a descriptive approach. The research subjects were 30 people, 28 women, and 2 men. Methods of data collection using observation and tests. The instruments used were observation sheets and tests. Data analysis was done with the reduction stages, data presentation, verification, and conclusion. From the results of the data analysis, it was found that the level of student creativity was already at the collaboration level. Students jointly divide tasks in preparing learning administration. It can be seen from the observations that each group makes a list of tasks that must be done. Judging from the work results, students have been able to arrange learning administration creatively. The creativity level of the project results is still at 75%. Several parts still need to be improved, such as learning objectives, materials, and forms of assessment that are outside of basic competencies. However, using project-based learning can instill creativity in students in producing products. Of course, further research is still needed to produce a good project.